Distinguishing computed tomography findings in patients with empty nose syndrome. Issue 10 (13th July 2016) - Thamboo, Andrew; Velasquez, Nathalia; Ayoub, Noel; Nayak, Jayakar V.
Abstract : Background: Given the lack of basic diagnostic criteria for empty nose syndrome (ENS), we sought to define whether consistent radiographic characteristics could be identified to aid in the development of such criteria. Methods: Computed tomography (CT) scans were collected from 65 patients diagnosed with ENS, patients with a history of submucosal inferior turbinate reduction (ITR) without ENS, and patients without a history of sinonasal procedures. Measurements were taken at the level of the nasolacrimal duct, including the inferior turbinate (IT) mucosal thickness, and the widest distances between septum‐IT, nasal floor‐IT, lateral nasal wall‐IT, and septum‐lateral nasal wall. The thickest sites of soft tissue density of the nasal cavity floor, septum, and lateral wall were also measured in the anterior, central, and posterior segments of the nasal cavity. Results: The mucosal thickness of both the central and posterior segments of the septum in ENS subjects was significant when compared to ITR without ENS ( p < 0.01) and control subjects ( p < 0.01). Constant landmarks such as the agger nasi, the presence of middle turbinate, and the nasolacrimal duct defined a simple set of landmarks that can serve as the start of the central‐nasal region, and a cutoff >2.64 mm and >1.32 mm in the central nasal and posterior nasal regions provided the highest likelihood of differentiating ENS patients from ITR without ENS patients. Conclusion: These findings provide evidence there are 2 objective radiographic changes (central and posterior septal mucosa) that suggest ENS patients can be discriminated based on mucosal CT findings.